Review of Neoleptastacus Nicholls, 1945 (Harpacticoida, Arenopontiidae), including an updated key to species and proposal of Phreatipontia gen. nov. - Sak, Serdar; Karaytuğ, Süphan; Huys, Rony (Zootaxa, 2024)
A revision of the genus Neoleptastacus Nicholls, 1945 (Harpacticoida, Arenopontiidae) is presented, resulting in the recognition of 24 valid species. The genus is divided in five species groups based on shared morphological character states, i.e. the acanthus-, australis-, speluncae-, trisetosus- and spinicaudatus-groups with the acanthus-group being further fragmented in three subgroups (acanthus, gussoae, ornamentus). The two members of the speluncae-group, Neoleptastacus phreatica (Cottarelli, Bruno & Venanzetti, 1994) and N. speluncae (Cottarelli, Bruno & Venanzetti, 1994), are redescribed and transferred to a new genus, Phreatipontia gen. nov., that appears to have a preference for low salinity habitats. The Mediterranean N. acanthus (Chappuis, 1954) is redescribed based on material from Türkiye and considered potentially conspecific with N. huysi (Karanovic, 2000). The male specimen illustrated in the original description of N. longiremis (Chappuis, 1955) is designated as the lectotype to define the nominal taxon objectively in the likely event that females and males assigned to this inadequately described species turn out to be non-conspecific. Detailed morphological comparison of species currently allocated to the gussoae-complex revealed three new cryptic taxa from Central and South America which are accorded specific rank (N. abbreviatus sp. nov., N. chilensis sp. nov., and N. rectus sp. nov.). The taxonomic status of Arenopontia (Neoleptastacus) acantha accraensis Lang, 1965 sensu Kunz (1971) is reassessed based on material from Angola and described as N. emendatus sp. nov. The Panamanian material previously identified as N. trisetosus (Mielke, 1982) is considered to represent a distinct species, N. panamensis sp. nov. while N. pseudishikarianus sp. nov. is proposed for the Chilean “population” of N. ishikarianus (Itô, 1968). Neoleptastacus supersetosus sp. nov. is described from Kuwait, representing the first arenopontiid record from the Arabian Peninsula. Neoleptastacus secundus Krishnaswamy, 1957 and N. accraensis (Lang, 1965) are treated as species inquirendae while Arenopontia breviarticulata Mielke, 1975 is removed from its provisional position in Neoleptastacus and placed as species incertae sedis in the Arenopontiidae. Distribution data are summarized for each species and the previously assumed amphi-Panamanian and amphi-Pacific distribution patterns of N. gussoae (Cottarelli, 1973) and N. ishikarianus, respectively, are rejected. Updated keys to the 24 valid species of Neoleptastacus and the six genera currently recognized in the family are provided.